Celiac disease prevalence and predisposing‐HLA in a cohort of 93 Williams‐Beuren syndrome patients. Issue 1 (18th October 2022) - Ghisleni, Cecilia; Parma, Barbara; Cianci, Paola; De Paoli, Anita; Pangallo, Elisabetta; Agovino, Teresa; Cereda, Anna; Bedeschi, Maria Francesca; Villa, Roberta; Fossati, Chiara; Modena, Piergiorgio; Giudici, Carolina; et al.
Abstract: Williams‐Beuren syndrome is considered to be at increased risk for celiac disease, as for recent literature data and celiac disease guidelines, despite pathogenic mechanisms are still unclear. Our study analyzed the prevalence of autoimmune disorders, HLA DQ2 and/or DQ8 haplotypes, of transglutaminase antibodies and of diagnosis of celiac disease in a cohort of 93 Williams‐Beuren syndrome's patients (mean age 21.26 years). Our study showed an increased prevalence of celiac disease equal to 10.8% (10/93 patients). We did not find a significant different frequency of predisposing HLA in subjects with Williams‐Beuren syndrome compared to literature data in the general population (49.5% vs. 42.9%, with p > .1), nor a susceptibility to autoimmunity. This suggests that the increased prevalence of celiac disease in Williams‐Beuren syndrome cannot be ascribed to HLA haplotype and may be related to other factors that still need to be identified in these patients.